A Quantitative Assessment of the Economic Viability of Photovoltaic Battery Energy Storage Systems - Aayesha S. Ahmad; Sumit K. Chattopadhyay; B. K. Panigrahi (Energies)
Rooftop PV-BESS installations often lose profitability despite policy support to accelerate capacity growth. This paper performs techno-economic analysis to assess the effect of heterogeneity in real-world conditions on the economic viability of residential rooftop PV-BESSs. The stochastic nature of generation and consumption is modeled as multiple deterministic scenarios that vary in the capacity rating of the PV system, climatic conditions (insolation and temperature), self-consumption ratio (SCR), generation–demand concurrence, and the presence/absence of capacity and storage subsidies. The results indicate that PV-BESSs are mostly profitable when operating at a capacity factor ≥ 18%. Furthermore, higher daytime electricity consumption enables greater savings with smaller storage capacities, thereby facilitating cost-effective installations at capacity factors ≥ 8%. However, low-yielding PV-BESSs and prosumers exhibiting low generation–demand concurrence require suitable subsidy allocations to become profitable.